Pseudohypoparathyroidism: a diagnosis to consider once a PTH elevation is detected - Brambilla, Ilaria; Rossi, Federico; Pistone, Carmelo; Licari, Amelia; De Filippo, Maria; Votto, Martina; Tondina, Enrico; Guarracino, Carmen (Acta Biomedica Atenei Parmensis, 2022)
Background and aim: Pseudohypoparathyroidism (PHP) is a rare disease, which can occur in the youth, characterized by hypocalcemia and hyperphosphatemia due to resistance to parathyroid hormone (PTH) in target organs. This condition encompasses different conditions which differ between one another by different clinical, biochemically, and genetic features.Methods: Herein we report the clinical history of a boy with PHP1B with an interesting clinical presentation. He came in fact to the attention of the Emergency Department because of a spontaneously resolving epileptic attack, lasting about 15 minutes, characterized by loss of consciousness, fall to the ground, tonic-clonic shocks, and sphincter release. Moreover, the personal history was characterized by congenital long QT syndrome (LQTS), with a documented mutation of the KCNQ1 gene, treated with beta-blockers (nadolol).Results: The simultaneous presence of symptomatic acute hypocalcemia and long QT syndrome undoubtedly required particular attention both in the management of the onset and in the more in-depth subsequent diagnostics. In this regard, laboratory tests and molecular analyzes have proved to be crucial in the diagnostic process. Conclusions: this case underlines the diagnostic path complexity in patients with PTH elevation and the importance of considering all the possible differential diagnoses in order to undertake a timely and correct course of treatment.